Intelligent cell-based therapies for cancer and autoimmune disorders. (December 2020) - Chen, Rui; Jing, Ji; Siwko, Stefan; Huang, Yun; Zhou, Yubin
Graphical abstract: Highlights: Emerging strategies to develop smart and controllable CAR T-cells. Devising CAR T-cells to overcome immunosuppressive tumor microenvironment. CAR engineering in natural killer cells and macrophages to expand immunotherapy. Engineered immune cells used to target autoimmune disorders. Abstract : Synthetic biology, when combined with immunoengineering (designated synthetic immunology), has enabled the invention of an arsenal of genetically encoded synthetic devices and systems to reprogram cells for therapeutic purposes. The engineered intelligent cells can serve as 'living' drugs to treat a wide range of human diseases including cancer, disorders of the immune system, and infectious diseases. As the most successful example, cells of the immune system engineered with chimeric antigen receptors (CARs) have shown curative potentials for the treatment of hematological malignancies. We present herein emerging approaches of designing smart CARs to improve their safety, specificity and efficacy in cellular immunotherapy, and describe latest advances in applying CAR-engineered immune cells to target cancer and autoimmune diseases.